Aquaponics Food Production Systems 2019
DOI: 10.1007/978-3-030-15943-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Plant Pathogens and Control Strategies in Aquaponics

Abstract: Among the diversity of plant diseases occurring in aquaponics, soil-borne pathogens, such as Fusarium spp., Phytophthora spp. and Pythium spp., are the most problematic due to their preference for humid/aquatic environment conditions. Phytophthora spp. and Pythium spp. which belong to the Oomycetes pseudo-fungi require special attention because of their mobile form of dispersion, the so-called zoospores that can move freely and actively in liquid water. In coupled aquaponics, curative methods are still limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(85 citation statements)
references
References 114 publications
0
85
0
Order By: Relevance
“…Aquaponics has been compared with aquaculture [2,7,8] and hydroponic [9][10][11][12] technologies in terms of production and profitability. Up to now, the research on aquaponics has been focused on sustainability [13][14][15], economic optimization [16][17][18], functional setup [19,20], stocking density [21,22], cultivation media [23,24], water recirculation [25,26], food safety [9,27], fish-plant pathogens [6,28] and beneficial microorganisms [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Aquaponics has been compared with aquaculture [2,7,8] and hydroponic [9][10][11][12] technologies in terms of production and profitability. Up to now, the research on aquaponics has been focused on sustainability [13][14][15], economic optimization [16][17][18], functional setup [19,20], stocking density [21,22], cultivation media [23,24], water recirculation [25,26], food safety [9,27], fish-plant pathogens [6,28] and beneficial microorganisms [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been demonstrated that a complete understanding of the hydroponic subsystem is essential to improving the whole aquaponics system [31]. One of the main difficulties related to aquaponics system is the potential dissemination of pathogens [6], because water recirculation and controlled parameters such as temperature provides the perfect environment for pathogen proliferation [28]. Evidence of previous outbreaks in aquaculture and hydroponics shows the consequences of such events.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…controlling water quality and aquaculture of aquaculture, based on these three mutually sustainable matters, a polyculture cultivation system was created to increase aquaculture production. Basically catfish have a pattern of life at the bottom of a pond or at the edge of a pond, while tilapia has a life pattern in the middle layer to the bottom of a water pool [2,3], so that with different aquatic habitats it is possible to cultivate together or ordinarily called a communal system. According to [4], fish commodities that support aquaponics cultivation are catfish, because catfish produce more fish feces than other fish.…”
Section: Introductionmentioning
confidence: 99%